Governance and counter-terrorism: Engaging moderate and non-violent extremist movements in combatting jihadist-linked terrorism. (March 2023) - Spalek, Basia; El-Awa, Salwa
Abstract: The increasing involvement of communities in counter-terrorism in the UK and Egypt in the 90s and the early years of the new millennium signals a shift from government to governance in these two countries. This article is an exploration of some of the key governance-related challenges and opportunities in involving mainstream and non-violent extremist Islamic movements in combating jihadist-linked terrorism. We discuss the complexity of engaging communities and moderate and non-violent extremist movements, emphasizing the importance of engaging communities in combating jihadist terrorism. We explore some key Islamist movements from an historical and ideological perspective and look at the involvement of these movements in violence and its prevention. We argue that UK policies in that respect have developed out of ideas of psychological and community resilience. Examples are drawn from the practical involvement of communities, including members of 'moderate' and of non-violent 'extremist' movements in combating terrorism.